CLINICAL FEATURES AND OUTCOME OF CEREBRAL ABSCESS IN CONGENITAL HEART DISEASE - Mehnaz, Atiq; Syed, Ahmed Umair; Saleem, Allana Salman; Khalid, Chishti N (Journal of Ayub Medical College Abbottabad, 2006)
Background: Cerebral abscess is a serious life threatening complication of several diseases. The objective of this study was to look at the clinical profile, microbiology and outcome of children with cerebral abscess having an underlying congenital heart disease as compared to other predisposing conditions. Methods: Thirty children aged less than 15 years were reviewed. There were 15 males and 15 females. The mean age of presentation was 5.6±4.4 years. Results: The duration of illness at the time of admission was 17.6±24.6 days. Typically patients presented with fever, vomiting, headache and seizures. The predisposing conditions found were cyanotic congenital heart disease in 11 (37%) of children, meningitis in 6 (20%), septicemia in 7 (23%) and no underlying cause was found in 5 (17%) children. The most common microbe in children with cyanotic congenital heart disease was of the Streptococcus milleri group (52%). Computerized tomography confirmed the diagnosis and the most common location of the abscess was the parietal lobe of the cerebral hemisphere. All abscesses were large, more than 2 cm in diameter and were aspirated surgically. Excision was performed in 6 children. Five children expired, one due to a intracranial bleeding and the others due to severe cerebral edema and tentorial herniation. Complications were seen in 20 children and 16 had sequelae, hemiparesis in 11 and seizure disorder in 5. Conclusion: Brain abscess is a serious infection with poor outcome if diagnosed late. Delayed surgical drainage has high morbidity and mortality. The threshold for diagnosis should be low particularly in children with a predisposing condition like cyanotic congenital heart disease. Key words: Brain abscess, cyanotic congenital heart disease